Beneficial Effects of Ursolic Acid and Its Derivatives—Focus on Potential Biochemical Mechanisms in Cardiovascular Conditions - Jakub Erdmann (MDPI AG, 2021)
Ursolic acid (UA) is a natural pentacyclic triterpenoid found in a number of plants such as apples, thyme, oregano, hawthorn and others. Several in vitro and in vivo studies have presented its anti-inflammatory and anti-apoptotic properties. The inhibition of NF-κB-mediated inflammatory pathways and the increased scavenging of reactive oxygen species (ROS) in numerous ways seem to be the most beneficial effects of UA. In mice and rats, administration of UA appears to slow down the development of cardiovascular diseases (CVDs), especially atherosclerosis and cardiac fibrosis. Upregulation of endothelial-type nitric oxide synthase (eNOS) and cystathionine-λ-lyase (CSE) by UA may suggest its vasorelaxant property. Inhibition of metalloproteinases activity by UA may contribute to better outcomes in aneurysms management. UA influence on lipid and glucose metabolism remains inconsistent, and additional studies are essential to verify its efficacy. Furthermore, UA derivatives appear to have a beneficial impact on the cardiovascular system. This review aims to summarize recent findings on beneficial effects of UA that may make it a promising candidate for clinical trials for the management of CVDs.